Temporal profile of expression and cellular localization of inducible nitric oxide synthase, interleukin-1β and interleukin converting enzyme after cryogenic lesion of the rat parietal cortex - Knerlich-Lukoschus, Friederike Friedel; Schilling, Lothar; Görlach, Christoph; Wahl, Michael; Ehrenreich, Hannelore; Sirén, Anna-Leena (Brain research. Molecular brain research, 1999)
We used in situ hybridization, RT PCR and immunohistochemistry to study the time course of expression and the cellular localization of inducible nitric oxide synthase (iNOS) and interleukin-1β (IL-1β) during the first 7 days after induction of a standardized cryogenic lesion on the right parietal cortex in male rats. Cryogenic lesion induced iNOS mRNA in the lesioned hemisphere after 6 to 72 h with a maximum (15±2 cells/mm2, n=4, p<0.01 vs. sham) at 24 h. Microglia, invading monocytes and granulocytes in and around the lesion expressed iNOS immunoreactivity starting at 12 h and peaking (29±10 cells/mm2, n=4, p<0.05 vs. sham) at 24 h after lesion. Induction of IL-1β mRNA expression was immediate with a peak (9±1 cells/mm2, n=4, p<0.01 vs. sham) at 24 h after cryogenic lesion. The number of round cells with IL-1β immunoreactivity around the lesion was maximal (8±2 cells/0.1 mm2, n=3, p<0.01 vs. sham) at 24 h. A weak astrocytic expression of IL-1β-immunoreactivity was seen in sham animal brains. Astrocytic IL-1β-expression was significantly increased in the lesion hemisphere and both hippocampi. Interleukin converting enzyme (ICE) was expressed in astrocytes and microglia around the lesion 6 h after injury. The number of ICE immunoreactive cells (8±2 cells/0.1 mm2, n=3, p<0.05 vs. sham) peaked at 72 h after lesion. Neuronal expression of ICE and IL-1β was seen in the lesion periphery 72 h and 7 days after injury. At this time, morphological features of apoptosis were evident in cells in the lesion periphery. The data indicate an early activation of microglia and monocyte invasion into the lesion hemisphere leading to multicellular expression of iNOS, ICE, and IL-1β. These events may contribute to the expansion of neuronal damage after brain injury.